Dealing with difficult days: functional coping dynamics in self-harm ideation and enactment - Nielsen, Emma; Sayal, Kapil; Townsend, Ellen (Elsevier, 2017)
Background: Self-harm affords people a means of coping. However, little is known about how functional coping dynamics differ between stressful situations in which people self-harm (enactment), think about harming (ideation), or experience no self-harmful thoughts or behaviours. Methods: Participants (N = 1,157) aged 16 − 49 years (M = 18.21, SD = 3.24) with a recent history of self-harm (past 3 months) reported how they coped in response to their most significant recent stressor (3 months). Results: Almost 40% of participants, all of whom had self-harmed in the last 3 months, had no self-harm experience (thoughts or behaviours) in response to their most significant stressor in that timeframe. In multivariate analysis, adjusting for symptoms of depression and anxiety, reappraisal coping was predictive of self-harm thoughts. Approach, emotion regulation and reappraisal coping were predictive of self-harm behaviour. Emotion regulation coping differentiated self-harm ideation and enactment groups. Limitations: The cross-sectional design of the study precludes the ability to make inferences regarding causality. Further, there is no agreed definition of ‘recent’ self-harm. Conclusions: Taken together, the findings suggest that functional coping dynamics may be differentially associated with self-harm ideation and enactment. This is important, given that understanding the transitions between ideation and enactment has been identified as a critical frontier in suicide prevention. Further, results indicate that seemingly innocuous events may have a profound impact as a tipping point for enaction; this has implications for clinical practice, including the co-production of safety plans.